Negotiation of Ideology in the Novel Series Rahvayana by Sujiwo Tejo - Liana Shinta Dewi; Muhammad Nur Hanif; Puri Bakhtawar (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to examine the negotiation that arise in the Rahvayana novel series by Sujiwo Tejo. This study uses the concept of ideology and negotiation by Antonio Gramsci and the concept of ideological response by John Clerke and Tonny Jefferson. This study uses observation and note-taking as data collection method. The data were analyzed using content analysis method with negotiation, ideology, and ideology responses as conceptual framework. The result show that there were ideological interactions and negotiations between wayang purwa and the Rahvayana novel series. The negotiation included negotiation of hierarchical ideology, authoritarian ideology, patriarchal ideology with relation ideology, egalitarian ideology, and feminist ideology. Nevertheless, there were several things that were kept preserved. For example, the relationship of Rahwana and his siblings, Rahwana’s feeling toward Sinta. It was shown that Sujiwo Tejo’s ideological response was negotiated.